PENGARUH KOMPLEKSITAS AUDIT, PROFITABILITAS KLIEN, UKURAN PERUSAHAAN, INDEPENDENSI DEWAN KOMISARIS DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP AUDIT FEE (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Hafiza Hafiza; Amir Hasan; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is to analyze the effect of audit complexity, client’s profitability, firm size, independency of the board commissioner and audit firm size to audit fee in manufacturing companies listed on Indonesia Stock Exchange from 2012-2015. This research used secondary data that is audited financial report which can be accessible through the website of Indonesia Stock Exchange www.idx.co.id. The population for this research is 135 manufacturing companies. The sampling method is purposive sampling. Based on this method, 45 companies are acquired as a sample, with 4 years of observation period. Thus, the sum of this research is 180 analysis unit. Then audit complexity, client’s profitability, firm size, independency of the board commissioner, audit firm size and audit fee are tested using multiple linear regression analysis using SPSS 21.0. Before being conducted the regression test, it is examined by using the classical assumption tests.The results of this research indicate that audit complexity, client’s profitability, firm size, independency of the board commissioner and audit firm size have a positive and significant effect on audit fee.Keywords : audit fee, audit complexity, client’s profitability, firm size, independency of the board commissioner, audit firm size